Characterization of genetics in patients with mucosal melanoma treated with immune checkpoint blockade. (15th March 2021) - Buchbinder, Elizabeth I.; Weirather, Jason L.; Manos, Michael; Quattrochi, Brian J.; Sholl, Lynette M.; Brennick, Ryan C.; Bowling, Peter; Bailey, Nancy; Magarace, Lisa; Ott, Patrick A.; Haq, Rizwan; Izar, Benjamin; et al.
Abstract: Mucosal melanoma is a rare form of melanoma which arises from melanocytes in the mucosal membranes and can be effectively treated with immune checkpoint blockade (ICB). However, response rates in mucosal melanoma are lower than those observed for cutaneous melanomas. Targeted sequencing of up to 447 genes (OncoPanel) was performed on tumors from all mucosal melanoma patients seen at the Dana‐Farber Cancer Institute from 2011 until March 2019. We identified a total of 46 patients who received ICB with both tumor‐genotype and ICB response data available. Within this cohort of patients, 16 (35%) had durable clinical benefit (DCB) to their first line of ICB. The average mutational burden/megabase was 6.23 and did not correlate with tumor response to ICB. Patients with KIT aberrations had a higher DCB rate compared with patients with wildtype KIT (71 vs. 28%), but this was not found to be statistically significant. For comparison, we analyzed tumor genotypes from an additional 50 mucosal melanoma tumors and 189 cutaneous melanoma tumors. The most frequent mutations in mucosal melanoma were in SF3B1 (27%), KIT (18%), and NF1 (17%), a pattern that is distinct from cutaneous melanomas. In addition, there were genetic differences observed based upon the site of origin of the mucosal melanoma. Our findings explore clinical features of response in patients with mucosal melanoma treated with ICB and demonstrate a low mutational burden that does not correlate with response. In addition, the lack of significant association between the genetic aberrations tested and response to ICB indicates the need for further exploration in this patient population. Abstract : Mucosal melanoma is a rare form of melanoma that arises from mucosal membranes within the nose, intestines or vaginal cavity. It can be treated with new immunotherapies that target immune checkpoints with some success but not all patients respond to these therapies. This study examines the genetic changes within mucosal melanoma to look for patterns that may help predict who will respond well to immunotherapy and who will not respond. Some interesting trends were observed but more work is needed to determine genetic mutations in mucosal melanoma that are associated with treatment.